Synthesis of Novel Graphene Oxide-chitosan-silicon Dioxide Nanocomposite Embedded in Polysulfone Membrane for Oily Water Treatment - Ahmed T. Yasir (17302753) (2024)
Oil and gas exploration activities result in generation of large quantities of produced water. Globally, for each barrel of oil, three barrels of produced water is generated. The oil content in produced water can vary between 3 and 20% depending on the location and age of the hydrocarbon well. Due to their hydrophobic nature, conventional hydrophobic polymeric membranes struggle to effectively separate oil from produced water. In this work, an innovative strategy is suggested by employing a hydrophilic/super-oleophobic nanocomposite to develop novel polymeric membranes able to effectively separate oil content from produced water without negatively affecting the other membrane properties such as the total flux and fouling. Graphene oxide-chitosan-silicone oxide (GO-CH-SiO2) nanocomposite was synthesized by functionalizing graphene oxide (GO) with chitosan (CH) and silicon dioxide (SiO2). To improve the membrane flux, anti-fouling propensity, and oil rejection, the synthesized nanocomposites were doped in the polysulfone membranes matrix. The effect of GO-CH-SiO2 concentration, GO:CH ratio, and GO-CH:SiO2 ratio on the performances of developed membranes was experimentally assessed, and morphology of the synthesized membrane was investigated using appropriate characterization techniques. The experimental results showed that the membrane with GO:CH of 1:2 and GO-CH: SiO2 ratio of 1:6.5 showed the highest pure water permeation flux of 28.35 LMH/bar with a comparable flux recovery rate of 76% and oil rejection efficiency of 98.5%. The study’s findings underscore the potential of GO-CH-SiO2 nanocomposite membranes for oil–water separation research, presenting a promising solution for treating produced water in the oil and gas industry. Further research is needed to scale up this technology and improve membrane performance by optimizing the nanocomposite composition and conducting long-term performance tests. Other Information Published in: Water Conservation Science and Engineering License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s41101-024-00313-4